2009
DOI: 10.1001/archdermatol.2008.602
|View full text |Cite
|
Sign up to set email alerts
|

Calciphylaxis With Normal Renal and Parathyroid Function

Abstract: Background: Calciphylaxis is a life-threatening form of metastatic calcification-induced microvascular occlusion syndrome. Although traditionally observed in patients with end-stage renal disease and/or hyperparathyroidism, the development of calciphylaxis in "nontraditional" patients having both normal renal and parathyroid function has been reported. However, to date there has been no collective analysis identifying common patient characteristics potentially predisposing to the development of calciphylaxis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
95
0
12

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 45 publications
2
95
0
12
Order By: Relevance
“…'Calciphylaxis in normal renal function' [17] consistently affects morbidly obese people suffering from arterial hypertension and type 2 diabetes as a result of their metabolic syndrome [7] . The disease is characterized by the rapid appearance of progressive skin infarctions in the regions of the inner thigh, fatty abdominal apron, breasts or outer upper arms -i.e.…”
Section: History Of Calciphylaxis With Normal Renal and Parathyroid Fmentioning
confidence: 99%
See 2 more Smart Citations
“…'Calciphylaxis in normal renal function' [17] consistently affects morbidly obese people suffering from arterial hypertension and type 2 diabetes as a result of their metabolic syndrome [7] . The disease is characterized by the rapid appearance of progressive skin infarctions in the regions of the inner thigh, fatty abdominal apron, breasts or outer upper arms -i.e.…”
Section: History Of Calciphylaxis With Normal Renal and Parathyroid Fmentioning
confidence: 99%
“…Ramsey-Stewart [18] described the entity as 'eutrophication', and Kalajian et al [17] reported on a series of patients under the more descriptive term 'calciphylaxis with normal renal and parathyroid function'. Hackett et al [19] reported successful treatment with sodium thiosulfate, shortly after the introduction of this modality, for the treatment of severe cases of classical calciphylaxis.…”
Section: History Of Calciphylaxis With Normal Renal and Parathyroid Fmentioning
confidence: 99%
See 1 more Smart Citation
“…It occurs in up to 4% of patients undergoing long-term dialysis, but sporadic instances in patients with normal renal function have also been reported. 1,2 In addition to kidney failure, other risk factors include obesity, female sex, white race, liver disease, use of systemic corticosteroids, decreased albumin levels and elevated calcium-phosphorus products. 2,3 Parathyroid hormone is often found to be abnormal.…”
mentioning
confidence: 99%
“…1,2 In addition to kidney failure, other risk factors include obesity, female sex, white race, liver disease, use of systemic corticosteroids, decreased albumin levels and elevated calcium-phosphorus products. 2,3 Parathyroid hormone is often found to be abnormal. Mortality associated with calciphylaxis is high, with an estimated one-year rate of survival of 45%.…”
mentioning
confidence: 99%